RELIGIOUS MODERATION EDUCATION THROUGH THE FRIDAY SERMON PULPIT IN CREATING A HARMONIOUS AND MODERATE SOCIETY - Suwarno, Suwarno; Suradji, Muchamad; Putra, Windisyah; Adlani, Nazril (Proceeding of International Conference on Islamic Education (ICIED); Vol 6 No 1 (2021): Proceeding of International Conference on Islamic Education (ICEID), 2021)
. In the last 10 years we have seen many phenomena about violence and coercion of will in the name of religion. For this reason, efforts are needed to prevent wider violence in the community. One of these efforts is through the pulpit of the Friday sermon which is moderate and polite. This study aims to look at the phenomenon of religious moderation education through the Friday sermon pulpit related to the prohibition of hajj in Surah al-Baqarah verse 197. The research method used in this study is a qualitative research method, data collection techniques are carried out by interview, data analysis with flow activities that occur simultaneously are: data reduction, data presentation, conclusion drawing/verification. The results of research on religious moderation education through the Friday sermon pulpit with the material on the prohibition of Hajj in Surah al-Baqarah verse 197 can create a harmonious and moderate life in society.